Criminal Liability And Law Enforcement Effectiveness Against Sound Horeg Organizers Causing Public Order Disturbances, Physical Harm, Loss of Life, and Ecosystem Damage - Raka Anugrah Valentino Erlangga; Widhi Cahyo Nugroho (Media Hukum Indonesia (MHI), 2026)
The rapid development of audio technology has popularized the use of high-volume sound systems known as "sound horeg" in community events such as carnivals, parades, and celebrations, particularly in East Java, Indonesia. This practice frequently exceeds safe decibel limits, leading to public order disturbances, health risks, property damage, and environmental harm including marine ecosystem disruption. This normative legal research analyzes the application of criminal sanctions and the effectiveness of law enforcement against sound horeg organizers under Indonesian positive law, focusing on the second research problem from the underlying thesis. Using statutory, conceptual, and case approaches, the study draws from the new KUHP (Law No. 1/2023), Environmental Protection Law (No. 32/2009), and related regulations. Findings reveal that while legal frameworks like Article 265 KUHP and Articles 98-99 of the Environmental Law provide bases for criminal liability (including corporate liability post-2026 reforms), enforcement remains weak due to reliance on administrative measures and restorative justice, lack of technical measurement tools, inter-agency coordination gaps, and cultural acceptance of the practice. Cases in Malang, Lumajang, and Pasuruan illustrate repeated violations with minimal deterrence. Recommendations include specific Perda regulations, enhanced technical capacity, integrated task forces, and balanced moderation approaches to harmonize cultural expression with public rights to a healthy environment.